Characteristics and outcomes of vaccinated and nonvaccinated patients hospitalized in a single Italian hub for COVID-19 during the Delta and Omicron waves in Northern Italy. (September 2022) - Rovida, Francesca; Esposito, Giuliana Lucia; Rissone, Marco; Novelli, Viola; Cutti, Sara; Muzzi, Alba; Rona, Claudia; Bertoli, Emanuela; Daglio, Marinella; Piralla, Antonio; Paolucci, Stefania; Campanini, Giulia; et al.
Highlights: Fragile individuals appear to be more susceptible to lower vaccine effectiveness. The Omicron variant seems to cause less severe COVID-19. During the Delta wave, a higher number of nonvaccinated individuals were admitted to the intensive care unit. Abstract: Objective: We compared the characteristics and outcomes of vaccinated and nonvaccinated patients hospitalized with COVID-19. Design: We analyzed patients hospitalized in a COVID hub during three one-month periods: (i) October 15, 2020-November 15, 2020 (prevaccination peak); (ii) October 15, 2021-November 15, 2021 (Delta wave); (iii) December 15, 2021-January 15, 2022 (Omicron wave). To define the epidemiologic context, SARS-CoV-2 infection in healthcare workers was analyzed. Results: SARS-CoV-2 infection incidence in healthcare workers was 146 cases per 1000 persons in 2020 (prevaccination) and 67 in 2021 (postvaccination, when the Omicron variant caused most infections). There were 420 hospitalized patients in the prevaccination period, 51 during the Delta wave (52.1% vaccinated) and 165 during the Omicron wave (52.9% vaccinated). During the Delta wave, a significantly higher number of nonvaccinated (29.2%) than vaccinated patients (3.7%) were admitted to the intensive care unit (ICU) (p = 0.019). Nonvaccinated patients were younger and had a lower rate of concomitant medical conditions (53.2% vs 83.7%; p < 0.001) during the Omicron wave when 80% of patients admitted to ICU and all those who died were still infected by the Delta variant. Conclusions: Vaccine effectiveness in fragile individuals appears to be lower because of a faster immunity decline. However, the Omicron variant seems to cause less severe COVID-19.